IoT Flood Monitoring System - Ajit Singh, Jaipreet Kaur; Huong, Audrey (Evolution in Electrical and Electronic Engineering, 2023)
Floods have occurred badly lately in some areas around Malaysia. It happens suddenly and affects a wide variety of people and buildings. Most people lack access to reliable knowledge about weather patterns and hence are unable to predict when the next flood will come. The main objective of this project is to develop and design an Internet of Things (IoT) flood monitoring system that is able to detect potential flooding conditions. This project consists of an ultrasonic sensor (HC-SR04) used to detect the height of the flood water in a laboratory-scale terrain modal for flood submergence simulation. A Durian UNO acts as a microcontroller in this system while the WIFI module (ESP-01S) is to send data from the microcontroller to the Blynk application. This system is also equipped with a buzzer, which would be activated once the flood water level passes a certain threshold value which is 5 cm and it would display on the “Liquid Crystal Display” (LCD) “HIGH” or “LOW”. Once exceeded the value, the system would then send an alert notification through the Blynk application and also display a real-time image of the flood on the user’s smartphone. This IoT flood monitoring system would help to alert its users about the presence of flood, thus saving human lives and properties in flood-prone locations.